Physical Module Validation Integrating Creative Thinking Ability in Measurement and Movement Materials - Hafizah, Nisaul; Hufri, Hufri (Department of Physics Universitas Negeri Padang, 2023)
The demands of the world of the future require children to have the creative thinking skills needed to develop science, technology and art. The chosen approach was to create a Physics learning module that incorporates students' creative thinking skills. The research conducted included the type of research and development and the object of the research was the Physics Module which was tested on high school class X students. This demonstrate employments 4 stages, specifically defining, designing, developing, and disseminating. Based on the comes about of the investigate that has been done, it can be concluded that the Physics Module integrates the ability to think creatively in the measurement and motion material that has been developed has a validity value of 71 in the valid category